Dividing a complex reaction involving a hypervalent iodine reagent into three limiting mechanisms by ab initio molecular dynamics. Issue 11 (12th March 2015) - Sala, Oliver; Lüthi, Hans Peter; Togni, Antonio; Iannuzzi, Marcella; Hutter, Jürg
Abstract : The electrophilic N ‐trifluoromethylation of MeCN with a hypervalent iodine reagent to form a nitrilium ion, that is rapidly trapped by an azole nucleophile, is thought to occur via reductive elimination (RE). A recent study showed that, depending on the solvent representation, the S N 2 is favoured to a different extent over the RE. However, there is a discriminative solvent effect present, which calls for a statistical mechanics approach to fully account for the entropic contributions. In this study, we perform metadynamic simulations for two trifluoromethylation reactions (with N ‐ and S ‐nucleophiles), showing that the RE mechanism is always favoured in MeCN solution. These computations also indicate that a radical mechanism (single electron transfer) may play an important role. The computational protocol based on accelerated molecular dynamics for the exploration of the free energy surface is transferable and will be applied to similar reactions to investigate other electrophiles on the reagent. Based on the activation parameters determined, this approach also gives insight into the mechanistic details of the trifluoromethylation and shows that these commonly known mechanisms mark the limits within which the reaction proceeds. © 2015 Wiley Periodicals, Inc. Abstract : Hypervalent iodine reagents such as λ 3 ‐iodanes are frequently used for electrophilic atom/group‐transfers. However, little is known about the mechanistic details of these reactions. Based on ab initio molecular dynamic simulations of the trifluoromethylation of two different nucleophiles with a λ 3 ‐iodane in acetonitrile solution, it is shown that the reaction may occur via three concomitant mechanisms (reductive elimination, nucleophilic substitution, radical mechanism), thus each one defining the limits in which the reaction may occur.